Pengaruh kualitas tidur dan dukungan sosial terhadap motivasi belajar mahasiswa - Dewinta, ST Mutiara; Eunike, Prisca (Universitas Darul Ulum, 2025)
Student learning motivation can be influenced by various factors, including sleep quality and social support. This study aims to examine the effect of sleep quality and social support on student learning motivation. This research employs a quantitative method with an accidental sampling technique. Data were collected through the distribution of questionnaires on social media. The participants in this study consisted of 212 university students in Indonesia aged 19-25 years. Data analysis was conducted using multiple linear regression tests with the JASP software. The hypothesis test results indicate that sleep quality does not affect learning motivation, whereas social support has an influence on learning motivation. Thus, social support is an important factor in enhancing student learning motivation.